Visualization analysis of knowledge graph of domestic self-regulated learning researches based on CiteSpace (基于CiteSpace的国内自我调节学习研究知识图谱可视化分析) - CHEN Qiannan (陈倩楠); QIAN Zhigang (钱志刚); WANG Beibei (王贝贝); JIN Guifang (金桂芳); ZHANG Xueru (张雪茹) (中西医结合护理)
Objective To analyze the development of self-regulated learning research in China based on CNKI database, and to provide reference for future research on the theory and practice of self-regulated learning. Methods "Self-regulated learning" was used as the search term, and the relevant literatures published on CNKI between January 1, 1994 and May 1, 2021 were searched. After screening, a total of 627 literatures were collected. The literatures were imported into CiteSpace software, and the publication time and journal distribution of the literatures were analyzed. Visual analysis of literature authors, institutions and keywords was conducted and knowledge map was drawn. Results The number of literatures published in China was 627, which showed an increasing trend. Cooperation between authors and institutions needs to be strengthened; The research focus ranges from the investigation and correlation analysis of the current situation of self-regulated learning to the reform of teaching model based on the theory of self-regulated learning, and finally to the intervention research of self-regulated learning. The research trend is to improve students' self-regulated learning ability through online learning intervention. Conclusion The research population of self-regulated learning is more and more wide, the research content and the research field are more and more detailed, but the cross research of self-regulated learning and medical discipline needs to be strengthened. (目的 基于中国知网数据库分析我国自我调节学习研究的发展状况, 为今后开展自我调节学习理论及实践研究提供参考。方法 以“自我调节学习”为检索词, 检索时间1994年1月1日—2021年5月1日发表于中国知网的相关文献。筛选后共获627篇文献, 将文献导入CiteSpace软件中, 对文献的发表时间、期刊分布进行数据分析; 对文献作者、机构、关键词进行可视化分析并绘制知识图谱。结果 国内文献发文量为627篇, 整体呈上升趋势; 作者间及机构间合作有待加强; 研究热点从自我调节学习现况调查及相关性分析到基于自我调节学习理论进行教学模式改革研究, 最后到自我调节学习的干预研究; 研究趋势为通过干预措施提高学生在线学习的自我调节学习能力。结论 自我调节学习的研究人群越来越广, 研究内容及研究领域越来越细化, 但自我调节学习研究和医学学科的交叉研究有待加强。)